Lithium Isotope Geochemistry in the Barton Peninsula, King George Island, Antarctica - Ryu, Jong-Sik; Lim, Hyoun Soo; Choi, Hye-Bin; Kim, Ji-Hoon; Kim, Ok-Sun; Vigier, Nathalie (Frontiers in Earth Science, 2022)
Lithium (Li) has two stable isotopes, 6Li and 7Li, whose large relative mass difference is responsible for significant isotopic fractionation during physico-chemical processes, allowing Li isotopes to be a good tracer of continental chemical weathering. Although physical erosion is dominant in the Polar regions due to glaciers, increasing global surface temperature may enhance chemical weathering, with possible consequences on carbon biogeochemical cycle and nutriment flux to the ocean. Here, we examined elemental and Li isotope geochemistry of meltwaters, suspended sediments, soils and bedrocks in the Barton Peninsula, King George Island, Antarctica. Li concentrations range from 8.7 nM to 23.3 μM in waters, from 0.01 ppm to 1.43 ppm in suspended sediments, from 9.56 ppm to 36.9 ppm in soils, and from 0.42 ppm to 28.3 ppm in bedrocks. δ7Li values are also variable, ranging from +16.4 to +41.1‰ in waters, from –0.4 to +13.4‰ in suspended sediments, from –2.5 to +6.9‰ in soils, and from –1.8 to +11.7‰ in bedrocks. Elemental and Li isotope geochemistry reveals that secondary phase formation during chemical weathering mainly control dissolved δ7Li values, rather than a mixing with sea salt inputs from atmosphere or ice melting. Likewise, δ7Li values of suspended sediments and soils lower than those of bedrocks indicate modern chemical weathering with mineral neoformation. This study suggests that increasing global surface temperature enhances modern chemical weathering in Antarctica, continuing to lower δ7Li values in meltwater with intense water-rock interactions.